The Function of Archives in the Effectiveness of Data Collection for Eligible Housing Program Recipients in Pasir Limau District Rokan Hilir Regency Cotton - Nining, Nining Prowoningsih Hsb (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
Archiving is an activity of placing and storing important documents in an organization, both companies and agencies, which aims to ensure the safety of an organization as written evidence, both in the form of pictures and so on. The purpose of this study was to determine the function of archives in the effectiveness of data collection for recipients of the livable housing program at the sub-district level. The type of research used is descriptive research with a qualitative approach. This study took as many as seven speakers. The data collection technique used in this research is interviews. The results of this study indicate that the supervision of the archives of livable houses is a task in the general section of the Public Housing and Settlement Areas Office and is assisted by technical implementing officials or PPTK, the sub-district only coordinates in data collection, not under supervision, the planning of the livable housing program has not been able to it is said to be precise and directed because there were obstacles in 2019 this program could not be continued due to the lack of government budget to continue the program and in 2020 this program has also planned to build 23 units but there are still obstacles due to the covid 19 virus which causes partial budgets disbursed for covid assistance. The livable house program has a clear goal of alleviating poverty but maximum efforts are needed so that this program assistance is more evenly distributed, the facilities and infrastructure provided in this program are only sanitation in every house, the physical building of the house is not strong enough so that this building cannot be used for a long period of time. Thus, archive managers should be more careful in choosing the criteria for recipients of the livable housing program so that the assistance provided is right on target to people who really need it. Keywords: archiving, effectiveness, data collection of livable houses.